Pengaruh Kepemilikan Manajerial dan Kepemilikan Institusional Terhadap Pemilihan Kantor Akuntan Publik pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Cok Istri Ratna Sari Dewi; Luh Putu Lusi Setyandarini Surya; Komang Adi Kurniawan Saputra (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
Agency conflict due to differences in interests between agents and principals can be minimized by monitoring mechanisms. One of the monitoring mechanisms is to use public accounting services. The purpose of this study is to determine the factors that influence the selection of public accounting firms by mining companies listed on the IDX in 2017. The selection of public accounting firms is measured by dummy variables. These factors include managerial ownership and institutional ownership. A sample of 35 companies was determined based on the purposive sampling method. The analysis technique used is logistic regression. Based on the analysis, the results show that managerial ownership has no effect on the selection of public accounting firms, while institutional ownership influences the selection of public accounting firms.